Cutaneous Basophil Hypersensitivity and Contact Sensitivity After Cutaneous Trichophyton mentagrophytes Infection - Green, Frederick (1980)
The histopathology of cutaneous lesions and trichophytin skin test responses was examined by light microscopy after the infection of strain 2 guinea pigs with Trichophyton mentagrophytes. Skin biopsies were fixed and stained with procedures which allowed differentiation of the polymorphonuclear granulocytic leukocytes that were present in lesions or skin test reactions. Basophils comprised about one-third of the leukocytes infiltrating the 24 to 48-h trichophytin skin test reactions of guinea pigs sensitized by a cutaneous T. mentagrophytes infection. These results were comparable to the percentage of basophils counted in skin test lesions elicited by the contact agent dinitrochlorobenzene and are consistent with previously published descriptions of cutaneous basophil hypersensitivity. In contrast, the active T. mentagrophytes lesion in the skin of guinea pigs sacrificed at defined intervals after infection or reinfection did not appear to contain similarly elevated numbers of basophils. The early inflammation in primary T. mentagrophytes-induced skin lesions can be characterized histologically as a primary irritant dermatitis which evolves, during the course of the disease, into a chronic mononuclear inflammation. This shift apparently results from host sensitization to fungal antigens during infection and the concurrent development of acquired immunity. Reinfection of guinea pigs with T. mentagrophytes resulted in an accelerated cutaneous inflammation that was temporally and histologically similar to allergic contact dermatitis. These results support the hypothesis that contact sensitivity to T. mentagrophytes develops during the primary cutaneous infection of guinea pigs and is an early component of the hypersensitivity response to reinfection.